The response of stock market volatility to futures-based measures of monetary policy shocks - Nikolay Gospodinov; Ibrahim Jamali (Federal Reserve Bank of Atlanta, 2014)
In this paper, we investigate the dynamic response of stock market volatility to changes in monetary policy. Using a vector autoregressive model, our findings reveal a significant and asymmetric response of stock returns and volatility to monetary policy shocks. Although the increase in the volatility risk premium, futures-trading volume, and leverage appear to contribute to a short-term increase in volatility, the longer-term dynamics of volatility are dominated by monetary policy's effect on fundamentals. The estimation results from a bivariate VAR-GARCH model suggest that the Fed does not respond to the stock market at a high frequency, but they also suggest that market participants' uncertainty regarding the monetary stance affects stock market volatility.
Keywords: C32; C58; E52; E58; G10; G12; 330; stock market volatility; federal funds futures; monetary policy; variance risk premium; vector autoregression; bivariate GARCH; leverage effect; volatility feedback effect